The Effect of Drought Stress on the Morphology and Anatomy of Codiaeum variegatum (L.) Rumph. ex A. Juss. and Excoecaria cochinchinensis Lour - Entin Daningsih; Galih Fathur Rahman; Pangesti Ayu Wandari Febriyani; Inka Febriyanti; Minati; Nadia Fransiska; Intan Permatasari; Ramadhan; Asih Perwita Dewi (Postgraduate, University of Mataram, 2025)
Climate change causes drought in many places, including tropical areas, which affects ornamental plants both in morphology and anatomy. Codiaeum variegatum (L.) Rumph. ex A.Juss. and Excoeceria cochinchinensis Lour have low transpiration rates and allow them to be resistant to drought. This study aims to observe the morphology and anatomy of C. variaegatum and E. cochinchinensis leaves due to drought stress. The experimental design was a factorial completely randomized design (2x2) with 3 replications. The main factors are two types of plants and two conditions namely control and drought. The combination was the interaction between the two main factors. Observations included descriptions of leaf blades and edges every week for four weeks. Stomata changes, description of stomata and leaf anatomical tissue were counted and measured using a microscope connected to optilab. Observation results showed changes in the appearance of leaf blades and leaf rolling. Stomata and SD varied as well as the thickness of leaf tissue which was differentiated in both thickness and shape. The conclusion of this research was that C. variaegatum was a drought tolerant plant and E. cochinchinensis was low tolerant. Both plants can aprropriately be used to green the area with water constrain as well as ornamental plants.